EVALUATION OF THE INCLUSION REALITY ON THE PUBLIC SCHOOLS OF FLORIANOPOLIS, SC (Human Factors in Design, 2012)
This article presents a descriptive study about the evaluation of the management of assistive technologies in educational unities of the Municipal network of Florianopolis that have in their class students with some kind of deficiency of incapacity. The study consisted in gathering of data about the current conditions of the management of the assistive technologies, from the point of view of teachers of the special educational care, teachers on classrooms, assistants and pedagogic supervisors. The results presented will guide multidisciplinary researches in design and ergonomics with the aim of suggesting solutions on assistive and communication technologies that allow the constant improvement and formation of the teachers, in the spirit of improving the capacity of learning and the social inclusion of handicapped children.